Evaluation of a rapid HIV testing initiative in an urban, hospital-based dental clinic. - Blackstock, Oni J; King, James R; Mason, Roger D; Lee, Cynthia C; Mannheimer, Sharon B (AIDS patient care and STDs, 2010)
Performing rapid HIV testing in nontraditional clinical settings such as dental clinics is a potential method for targeting high-risk individuals who may not otherwise access health care settings that offer HIV testing. In March 2008, Harlem Hospital Center, located in New York City, launched a counselor-based rapid HIV testing initiative in its on-site dental clinic. A full-time, trained counselor consented and tested patients as they waited for their appointments. HIV screening was performed using a whole-blood, finger-stick rapid HIV test. Through this initiative, 3864 HIV tests were performed from March 1, 2008 to December 31, 2009, representing 3565 unique individuals and 97.6% of dental patients approached for testing. Of those tested, the mean age was 38.5 years, with 47.1% female, 75.5% black, and 20.6% Hispanic. Self-reported HIV risk behaviors included 73.5% with recent unprotected heterosexual intercourse, 4.6% with recent or past injection drug use, and 2.6% who identified as men who have sex with men. Nineteen previously undiagnosed individuals (0.53%) were confirmed HIV positive. Of these individuals, mean age was 38.3 years with males representing 84.2%. Fifteen newly diagnosed patients (78.9%) were linked to care. Of those linked to care, median initial CD4 cell count was 317 cells/mm(3); 6 of these individuals (40%) had CD4 cell counts below 200 cells/mm(3). Our results demonstrate that a counselor-based rapid HIV testing program with linkage to specialized HIV care can be successfully integrated into the dental clinic setting.
Keywords: Adult; AIDS Serodiagnosis; Counseling; Delivery of Health Care, Integrated; Dental Clinics; Female; HIV Infections; HIV-1; Hospitals, Urban; Humans; Male; New York City; Patient Acceptance of Health Care; Time Factors